INTEGRASI METODE BALANCED SCORECARD DAN SISTEM MANAJEMEN PENGENDALIAN - Sriwidadi, Teguh (Bina Nusantara University, 2012)
This article discusses sales force performance measurement at PT Merapi Utama Pharma and integrates performance measurement and management control system. The balanced scorecard (BSC) is a strategic planning and management system that is used extensively in business and industry, government, and nonprofit organizations worldwide to align business activities to the vision and strategy of the organization, improve internal and external communications, and monitor organization performance against strategic goals. The balanced scorecard suggests that we view the organization from four perspectives : the learning and growth perspective, the internal business processes perspective, the customer perspective, and the financial perspective.The management control system used is levers of control framework, included beliefs control system, boundary control system, diagnostic control system, and interactive control systems.Â